Enhanced Originality of Ideas in Women During Ovulation: A Within-Subject Design Study - Galasinska, Katarzyna; Szymkow, Aleksandra (Frontiers in Psychology, 2022)
The signaling theory suggests that creativity may have evolved as a signal for mates. Indeed, its aesthetic value might not have been necessary for survival, but it could have helped to attract a mate, fostering childbearing. If we consider creativity as such a signal, we should expect it will be enhanced in the context related to sexual selection. This hypothesis was tested mainly for men. However, both men and women display physical and mental traits that can attract a mate. Previous studies showed that women can be more creative during their peak fertility. We advanced these findings in the present study, applying reliable measures of menstrual cycle phases (examining saliva and urine samples) and the highly recommended within-subject design. We also introduced and tested possible mediators of the effect. We found women’s ideas to be more original during ovulation compared to non-fertile phases of the ovulatory cycle. The results are discussed in the context of signaling theory and alternative explanations are considered.